Subboiling Moist Heat Favors the Selection of Enteric Pathogen Clostridium difficile PCR Ribotype 078 Spores in Food - Alexander Rodriguez-Palacios; Sanja Ilic; Jeffrey T. LeJeune (Canadian Journal of Infectious Diseases and Medical Microbiology)
Emerging enteric pathogens could have not only more antibiotic resistance or virulence traits; they could also have increased resistance to heat. We quantified the effects of minimum recommended cooking and higher temperatures, individually on a collection of C. difficile isolates and on the survival probability of a mixture of emerging C. difficile strains. While minimum recommended cooking time/temperature combinations (63–71°C) allowed concurrently tested strains to survive, higher subboiling temperatures reproducibly favored the selection of newly emerging C. difficile PCR ribotype 078. Survival ratios for “ribotypes 078” :  “other ribotypes” (n=49 : 45 isolates) from the mid-2000s increased from 1 : 1 and 0.7 : 1 at 85°C (for 5 and 10 minutes, resp.) to 2.3 : 1 and 3 : 1 with heating at 96°C (for 5 and 10 minutes, resp.) indicating an interaction effect between the heating temperature and survival of C. difficile genotypes. In multistrain heating experiments, with PCR ribotypes 027 and 078 from 2004 and reference type strain ATCC 9689 banked in the 1970s, multinomial logistic regression (P<0.01) revealed PCR ribotype 078 was the most resistant to increasing lethal heat treatments. Thermal processes (during cooking or disinfection) may contribute to the selection of emergent specific virulent strains of C. difficile. Despite growing understanding of the role of cooking on human evolution, little is known about the role of cooking temperatures on the selection and evolution of enteric pathogens, especially spore-forming bacteria.